Comovements in Stock Prices and Comovements in Dividends - SHILLER, ROBERT J. (Journal of Finance, 1989)
ABSTRACT The comovements in real stock prices between the U.K. and the U.S. appear to be too large to be accounted for in terms of the comovements of real dividends between the countries even after consideration of the possibility of information pooling. When consideration is made of the comovements of real interest rates between the countries, there is weaker evidence of excess comovement of price.